Design and Control System Monitoring of Water Quality on Tilapia Cultivation Farm based Internet of Things (IoT) with NodeMCU - Fathimah Nur Afifah; Emy Haryatmi (Universitas Islam Sumatera Utara, 2020)
Fish cultivation has a high potential to improve the welfare of the community. One of the important factors influencing the success of fish cultivation is the aspect of water quality in the pond which is illustrated by several physical parameters such as temperature, degree of acidity (pH) and turbidity of the water. The use of water for cultivation must always be maintained at turbidity level, the impact of turbid water causes disruption to the physical growth of the fish and even death. Due to the limitations of humans who cannot monitor ponds 24 hours, a system is created that can monitor and control water quality in real time. To get good water quality for cultivation, the authors make this system using a turbidity sensor to detect water turbidity, a pH sensor to detect the acidity of the water and a temperature sensor to detect the temperature of the water on the pond. While processing and control using a microcontroller, namely NodeMCU. Periodically the sensor will send the measurement results to the Cayenne application in real time which can be viewed via a smartphone / PC. The control system is also made with two modes, namely automatic and manual modes to fill and drain water on the pond. Based on the results of system testing, turbidity, pH and temperature sensors are very good in detecting any changes in pond water conditions. Cayenne application with IoT technology is able to provide action on the water pump in the process of draining and filling water in ponds with manual mode. NodeMCU is able to send data with a good internet connection.